A scientometrics study of the nanomedicines assisted in respiratory diseases - Yang, Yi; Luo, Dexu; Inam, Muhammad; Hu, Jialin; Zhou, You; Xu, Chuanshan; Chen, Wenjie (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomedicine has been extensively studied for its versatility and broad-spectrum applications of theranostics in the research of respiratory disease. However, to the best of our knowledge, a scientometrics study based on the scientific knowledge assay of the overall situation on nanomedicine applied in the research of respiratory disease has not been reported so far, which would be of major importance to interior researchers. To explore and exhibit the research status and developing trend of nanomedicines deployed in basic or clinical research in respiratory disease, the research ecosystem, and exciting subareas were profiled based on the massive data mining and visualization from the relevant works reported from 2006 to 2021. Data were collected from the Web of Science database. Data statistics software and bibliometric analysis software were employed to visualize the research trend and the relationship between respiratory diseases and nanomedicines in each representative direction. The cluster analysis and burst detections indicated that the improvement of drug delivery and vaccine developments are the up-to-date key directions in nanomedicines for respiratory disease research and treatments. Furthermore, we emphatically studied four branch areas in this field including COVID-19, nanotube, RSV, and mRNA vaccine those are selected for in-depth mining and bibliometric coupling analysis. Research trends signify the future focuses will center on preventing respiratory diseases with mRNA vaccines using nanoparticle-based approaches. We anticipate our study will enable researchers to have the panorama and deep insights in this area, thus inspiriting further exploitations especially the nanobiomaterial-based systems for theranostic applications in respiratory disease treatment.